Feeling Attached to Symbolic Brands within the Context of Brand Transgressions - Sayin, Eda; Gürhan Canli, Zeynep (Emerald, 2015)
Purpose We propose that brands with strong associations and dedicated customers may be vulnerable if customers perceive them as exploiting their relationship. Methodology/approach We start by reviewing the literature on brand meaning, brand attachment, brand relationships, and brand transgressions. The extant literature implies that as a result of their willingness to sustain their brand relationship, highly attached consumers will either discount negative information about a brand or attribute the responsibility for the negative information to some external factors. We propose, on the other hand, that when negative information dilutes the reason for brand attachment, the norm of the consumer–brand relationship is violated (brand transgression). Then we argue that highly attached consumers of that brand will react more negatively (when compared to consumers not feeling highly attached) toward the brand. Findings We introduce a typology of brand transgressions against the (1) expressive, (2) exclusive, (3) expert, and (4) empathic nature of brands. We discuss the possible effects of attachment levels on consumers’ reactions after such brand transgressions. Additionally, we articulate the moderating effects of four consumer motives (need for self-enhancement, need for uniqueness, need for risk avoidance, and need for justice) on consumer reactions. Originality/value Our reasoning counters the literature suggesting that highly attached consumers of a brand will engage in relationship-sustaining behaviors. We contribute to the brand-transgression literature by providing a more structured and detailed definition of brand transgressions by classifying them under four distinct types.
Keywords: ODS 10 - Reducción de las desigualdades